PENGEMBANGAN E-LKPD BERBASIS PROBLEM BASED LEARNING PADA MATERI BANGUN RUANG KELAS V - Putri, Kharisma; Rahayu, Sri; Sesanti, Nyamik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study originates from the need to provide digital-based learning resources in the form of Student Worksheets (LKPD) integrated with the Problem Based Learning (PBL) approach. The primary aim of this research is to design and develop an electronic PBL-oriented LKPD on the topic of three-dimensional geometry for fifth-grade elementary school students, which meets the criteria of validity, practicality, and effectiveness as a teaching medium. The research employed the ADDIE model, encompassing analysis, design, development, implementation, and evaluation stages. The subjects of the study were fifth-grade students, with data collected through expert validation questionnaires, teacher and student response surveys, as well as learning outcome assessments. Validation results indicated that the material component achieved 72.5% (valid), the media aspect reached 90% (highly valid), and the language aspect scored 96.87% (valid category). Practicality testing with teachers produced 85.5% (highly practical), while student responses reached 86.57% (highly practical). Effectiveness testing showed a score of 94.66% (effective category). Overall, the findings demonstrate that the PBL-based electronic LKPD on three-dimensional geometry for fifth-grade students was successfully developed and fulfilled the standards of validity, practicality, and effectiveness as a learning medium.